(untitled) (CIPEEX, 2022)
The theme of the study is the practice of scouting and its psychoeducational and socio-environmental benefits observed in children and adolescents. This investigation will encompass the historical relationships of the Scout Movement; a field study will be conducted at the Bernardo Sayão Scout Group and observations will be made regarding the scouts’ concern with environmental issues and sustainability through the "Tribe of the Earth" activity. The psychosocial benefits of children participating in camping with outdoor activities in nature and the perception of their families will be verified. Through the obtained results, a data triangulation will be conducted to better understand its objectives. The theoretical framework will be based on the concepts of Scouting, Child and Adolescent Rights, Environmental Law, Education, Ecological Psychology, drawing on different theoretical contributions and engaging with various authors. The methodology will be a research with a qualitative-quantitative approach, hermeneutic method, data collection at the Juvenile Court, analysis/research of legislation, questionnaires, fieldwork, and content analysis technique. Diagnostic studies will be important to visualize the current scenarios that these initiatives face and to envision perspectives and strategies capable of enhancing them. Considering that scouting plays an important role in the construction of values and socio-environmental awareness among participants, this research aims to understand the psychosocial benefits arising from proximity to nature and to verify the restorative effect that natural environments provide to children and adolescents.